Analisis Sentimen Kritik dan Saran Layanan RSUD Akhmad Berahim Tana Tidung menggunakan Metode Lexicon-Based - Maulidia, Nurmala; Praseptian M, Dikky (Journal of Big Data Analytic and Artificial Intelligence, 2025)
Rapidly developing information technology must become a significant component in its use in all human life to simplify work. This matter underlined the research with that title, which the author believes will be an element of service assessment, whether positive, negative, or neutral. Sentiment analysis is required while evaluating a service, particularly in hospitals. The Lexicon-Based method uses a dictionary or lexicon as a language basis. This method classifies a sentiment from each opinion so that a sentiment sentence can be classified as positive, neutral, or negative. The text data will then be calculated using a Lexicon-Based to produce service quality sentiment analysis. The research used 100 data, with a questionnaire distributed of as many as 90 data and a suggestion box of as many as 10 data for sentiment analysis. The research received data of 33 criticisms and 67 suggestions. The Lexicon-Based method also classifies data into positive, negative, and neutral. The designed system can assist hospitals in evaluating services.